Computer safety, reliability, and security : SAFECOMP 2016 Workshops, ASSURE, DECSoS, SASSUR and TIPS Trondheim, Norway, September 20, 2016, proceedings /: SAFECOMP 2016 Workshops, ASSURE, DECSoS, SASSUR and TIPS Trondheim, Norway, September 20, 2016, proceedings. (2016) - Unknown
No abstract available